The Oxford companion to chess - Hooper, David, 1915- (Oxford University Press, 1984)
From the earliest myths describing the games invention right up to the semi-finals of the 1993 World championship cycle, this book embraces all branches of the game, including over-the-board play, correspondence chess and other forms of telechess. Biographies of all major figues are also included.